Preparation and characterization of cotton fabrics with antimicrobial properties through the application of chitosan/silver-zeolite film - Scacchetti, Fabio A. P. (2017)
The development of antimicrobial cotton fabrics using chitosan/silver-zeolite film has been investigated in the present work. The film was applied to 100% cotton fabric using a common pad-dry-cure technique and citric acid was used as crosslinking agent. The resulting fabrics were characterized through infrared spectroscopy (FTIR), contact angle and scanning electron microscopy with X-ray microanalysis (SEM/EDS). The antimicrobial activity of the fabrics was assessed through the viable-cell counting method and the materials showed activity against S. aureus and T. rubrum. The textile performance of the fabrics was analysed regarding their characteristics of hydrophilicity and breathability. The finishing did not change the hydrophilic behaviour of the material. Although the permeability to air has reduced 20%, the permeability to water vapour remained practically unchanged. Therefore, the results suggested that the process approach of applying chitosan/silver-zeolite film is recommended to produce textiles with antibacterial properties.